دراسة التشوهات البولية المرافقة للسلس البولي البدئي عند الأطفال - أصلان سمير; خوري مها; الشنتوت طاهر (Latakia University Journal -Medical Sciences Series, 2019)
مقدمة : اضطرابات التبويل مشكلة شائعة عند الأطفال ، وتترافق في بعض الحالات مع تشوهات بولية هامة. هدف الدراسة : تحديد نسبة وعوامل خطورة التشوهات البولية المرافقة للسلس البولي البدئي عند الأطفال. طريقة الدراسة: أجريت هذه الدراسة المستقبلية في مستشفى الأسد الجامعي في اللاذقية بين 1/11/2007 و1/5/2009 ، وشملت 100طفل (5-14 سنة) تم تقسيمهم إلى : المجموعةA تشمل مرضى السلس البولي الليلي البدئي المعزول ، وتضمنت 69 طفلاً(%69 ، ذكور 43: إناث 26) ، والمجموعةB تشمل مرضى السلس البولي البدئي النهاري، وتضمنت 31 طفلاً (%31 ، 18:13) ، وقد تم تقييم المرضى سريرياً وشعاعياً (تخطيط الصدى، تصوير الحويضة عبر الوريد ، تصوير المثانة والإحليل الإفراغي) . النتائج: لم تشخص نسبة هامة من التشوهات البولية في المجموعةA ، بينما شخصت نسبة هامة منها(22.58%) لدى مرضى المجموعة B ، وكان أشيعها الجذر المثاني الحالبي ثنائي الجانب (19.34%) . الخلاصة: لا يترافق السلس البولي البدئي الليلي المعزول مع زيادة خطورة التشوهات البولية ، بينما يترافق السلس البولي البدئي النهاري بشكل هام مع التشوهات البولية, وبشكل خاص الجذر المثاني الحالبي . Background: Voiding dysfunction is a common problem in children, and is sometimes associated with urinary malformations. Objective: This study aims at determining the prevalence and the risk factors of the urinary malformations that are associated with the primary urinary incontinence in children. Method: This prospective study was performed at Al-Assad AcademicHospital in Lattakia between 1/11/2007and 1/5/ 2009 and included 100 children(5 to 14 years) that were divided to two groups: - GroupAincluded isolated monosymptomatic primary nocturnal enuresis patients, and contained 69child (69%; males 43: females 26).Group B included daytime primary urinary incontinence patients, and contained 31 children (31%; 13:18). Patients were evaluated clinically, and by urologic imaging (ultrasonography, IVP, CVUG). Results: No important rate of the urinary malformations was diagnosed in group A, while an important rate of it was diagnosed in group B (22.58%), and the most famous was the vesicoureteral reflux (19.34%). Conclusion:Isolated mono-symptomatic primary nocturnal enuresis does not associate with any increase in the rate prevalence of the urinary malformations, where the daytime primary urinary incontinence associates with the urinary malformations in a significant rate, and the most famous of it was the vesicoureteral reflux.